Criteria For Choosing The Cement Type For The Manufacture Of Water Resistance Concrete - Ashot Antonyan (International Journal of Advanced Science and Technology, 2020)
The sustainable development concept of modern civilization takes into account the interests of future generations, which in general in all sectors of life determines the use of resource-saving technologies, the secondary use of materials, the creation of waste-free production, the reduction of maintenance costs, the reduction of energy consumption, and the reduction of harmful substances into the atmosphere. Construction materials science in general, and concrete science in particular, involves the development of this concept by dramatically increasing the durability of products and constructed structures. Therefore, the study of the theory and practice of durable concrete is an extremely urgent task.